Application of the Discovery Learning Learning Model in Thematic Lessons in Elementary Schools - Rumpoko Dewi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Discovery learning is a learning model based on experience where students are expected to be able to investigate on their own, build experience, be able to develop their creativity so that they arrive at a conclusion. The purpose of this article is to be used by teachers in designing thematic learning plans in elementary schools that can encourage students to think critically, develop their knowledge based on experience and train students to solve problems. The Discovery Learning learning model is a learning model that actively involves students, where delivery is by providing stimulation or stimulation to students about a problem, then identifying the problem by collecting some data so as to train students to think critically, be active, and have fun.